Evaluation and assessment of the constitutionality of penitentiary decisions, in the light of the introduction of the penitentiary credit system - Ágnes Czine (Belügyi Szemle)
Aim: Criteria for the evaluation by the Constitutional Court of decisions on the execution of sentences.